2018
DOI: 10.3382/ps/pex261
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary Lactobacillus rhamnosus CF supplementation on growth, meat quality, and microenvironment in specific pathogen-free chickens

Abstract: The probiotic effects of Lactobacillus rhamnosus strain CF (Chen Fu) on growth performance, meat quality, and microenvironment in specific pathogen-free (SPF) chickens were investigated and compared with Enterococcus faecium. One-hundred-eighty 7-day-old SPF chickens were randomly assigned into 3 groups with 3 replicate pens of 20 chickens each. Group 1 served as a control that was fed a basal diet without probiotics supplementation. Groups 2 and 3 were fed the basal diet supplemented with L. rhamnosus CF and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
18
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 28 publications
2
18
1
Order By: Relevance
“…In our study, L. rhamnosus and L. curvatus were only found in broilers treated with the Synbiotic mix, while L. pentosus, L. buchneri , and L. mesenteroides were found exclusively in broilers that did not receive the Synbiotics. L. rhamnosus improves growth performance, meat quality, ammonia emission, and intestinal microbiota in chickens [60]. Lactobacillus curvatus display antimicrobial activity against Klebsiella, E. coli , and Staphylococcus aureus [61].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, L. rhamnosus and L. curvatus were only found in broilers treated with the Synbiotic mix, while L. pentosus, L. buchneri , and L. mesenteroides were found exclusively in broilers that did not receive the Synbiotics. L. rhamnosus improves growth performance, meat quality, ammonia emission, and intestinal microbiota in chickens [60]. Lactobacillus curvatus display antimicrobial activity against Klebsiella, E. coli , and Staphylococcus aureus [61].…”
Section: Discussionmentioning
confidence: 99%
“…Many probiotics, including BS, have been approved as animal diet supplement and are already used in many commercial applications (Cutting, ; Griggs & Jacob, ). A growing body of scientific research shows that probiotics have beneficial effects on growth performance and intestinal microbiota balance in chickens (Chen, Gao, Zhu, Qin, & Qiu, ), piglets (Lan, Tran, & Kim, ) and aquaculture (Liu, Chiu, Wang, & Cheng, ; Niamphithak, Chareonwattanasak, & Doolgindachbaporn, ). Dietary BS exerts positive effects on production performance, improving the intestinal health and systemic immunity in poultry (Hatab, Elsayed, & Ibrahim, ; Lee, Lillehoj, Jang, & Lee, ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some studies showed that combined use of probiotics could promote growth performance in animals [ 35 , 36 , 37 , 38 ]. However, some research showed that combined use of probiotics exerted no significant effect on growth performance [ 39 ].…”
Section: Discussionmentioning
confidence: 99%